A virtual issue highlighting animal studies of eating disorders as valuable tools for examining neurobiological underpinnings and treatment of eating disorders. Issue 9 (3rd June 2020) - Fowler, Natasha; Klump, Kelly L.
Abstract: While studies in humans suggest a role for psychosocial factors as well as biological and genetic processes in the development of eating disorders, the specific etiologic mechanisms remain largely unknown. In this virtual issue, we present a collection of 14 archived articles from the International Journal of Eating Disorders to highlight the utility of animal studies of eating disorders to advance our understanding of eating disorder etiology. Selected articles establish animal studies as valid tools to study disordered eating behavior, offer insight into potential neurobiological mechanisms, and highlight novel targets for future pharmacological treatments. Clinical implications of each article's findings are included to demonstrate the translational value of animal studies for the eating disorders field. We hope that the exciting concepts and findings in this issue inspire future animal studies of eating disorders.